UPAYA GURU DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH IBADAH MELALUI METODE DEMONTRASI - Ayu Puji Rahayu; Riska Apriyanti (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2021)
In schools, teachers and students are the main actors in the learning process. Both play an important role in achieving learning objectives. Teachers as one of the learning resources are obliged to provide a creative learning environment for students' learning activities in class. Fiqh learning in MTs aims to equip students to know and understand the points of Islamic law in detail and thoroughly, both in the form of naqli and aqli evidence. The objectives of this study are as follows; 1. Knowing how teachers' efforts in improving students' learning outcomes in fiqh learning of grade VII prayer materials at MTs. Miftahul Ulum Gununghalu; 2. Knowing how to apply demontration method in fiqh learning of grade VII prayer material in MTs. Miftahul Ulum Gununghalu; 3. Know how students learn from the application of demontrasi method in fiqh learning of grade VII prayer material in MTs. Miftahul Ulum Gununghalu. The research method used is class action research (PTK), with two cycles. While the results showed in the first cycle of posttest results, students achieved a minimum completion criteria of 75. While in the second cycle, posttest results showed excellent learning results that reached an average of 85.